Providing explanations by regional chambers of audit in matters relating to an application of provisions on public finances. Legal, practical and problematic issue - Kamil Krauschar (Prawo Budżetowe Państwa i Samorządu)
Following the clara non sunt interpretanda clause, the concept of an interpretation of universally applicable law, corresponding to a principle of the Community law of the European Union – acte clair, has been established in judicial and administrative judgments, which is based on an interpretation of law, only in cases of doubts as to the clarity and understandability of a legal text. Local government units participate in the exercise of public authority, and a significant part of public tasks vested in them by the self-government on their own behalf and on their own responsibility. Moreover, owing to a need to respect the principle of the rule of law, thus to interpret the norms of law correctly, the units are obliged to take factual and legal actions, regulating a legal relationship at their own will, externalized by representative bodies. Correct understanding of a legal text or decoding it through interpretation is a follow-up activity to the cited parema, it is “an unquestionable component of the legal culture on the basis of which the discourse related to operative interpretation takes place”. Regional accounting chambers, which exercise supervision and control, but also implement statutory competences in the field of providing explanations in matters relating to the application of provisions on public finances, create basis for conducting an examination of the issues of an application of a financial law by local government units, based on its practical aspects. The aim and scope of the publication is an attempt to obtain an answer to the theses presented in it. An analysis of the current jurisprudence of regional chambers of audit, administrative courts and the Constitutional Tribunal complement deliberations of the doctrine. The presented publication is an attempt to comprehensively approach the issue in a theoretical and practical way.